AN UNUSUAL LARGE SIZE DUCTAL CARCINOMA IN SITU IN A PATIENT ON LITHIUM THERAPY: A CASE REPORT WITH LITERATURE REVIEW - Jabeen, Dua; Mushtaque Vohra, Lubna; Siddiqui, Tariq; Zeeshan, Sana (Journal of Ayub Medical College Abbottabad, 2022)
Background: Ductal carcinoma in situ (DCIS) is the earliest and most curable form of breast cancer. Patients who harbour this disease for quite some time usually have micro invasion by virtue of high-grade disease or big size. Herein, we report a case of 56-year-old postmenopausal woman presenting with a one-year history of blood-stained nipple discharge from right breast. She was a known case of depression receiving oral anti-depressants containing lithium for 20 years. Her mammogram was performed followed by ultrasound breast. Mammogram identified suspicious clusters of micro calcifications hence subjected to stereotactic core biopsy which revealed two separate foci of high-grade DCIS. Therefore, based on her clinical, radiological, and pathological findings she was subjected to mastectomy and sentinel node biopsy. Final histopathology showed big DCIS (10Ã—8Ã—3 cm in size) with immunohistochemical stains confirmed no invasive focus on extensive sampling. Therefore, we postulated that it might be correlated to the use of Lithium which has anti-cancer properties.